2018
DOI: 10.1088/1361-6463/aaa0ee
|View full text |Cite
|
Sign up to set email alerts
|

Substantial difference in target surface chemistry between reactive dc and high power impulse magnetron sputtering

Abstract: Advanced functional coatings with applications ranging from wear-resistant layers on cutting tools [1,2] to diffusion barriers in electronic devices [3,4] are often produced with the advantage of reactive magnetron sputtering under high vacuum conditions. The presence of a reactive gas, however, leads not only to the desired compound formation at the substrate, but also to a simultaneous chemisorption at the target that is covered with a compound layer by so-called target poisoning. This results in severe redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Nevertheless, extensive effort was made in this study to meet the constraints on peak position, doublet separation and doublet area ratio simultaneously as much as possible. It should be noted that centering the TiN 2p 3/2 peak at around 455.85 eV, , near the upper limit of the possible range, produced the best fitting overall for our data, even though some studies have fitted the same peak to around 455.3 eV. , In addition, when the difference in the C–C binding energy between the values in this study (284.6–285.1 eV for samples produced at plasma powers at or above 75 W) and the value suggested in the detailed study on adventitious carbon contamination on TiN films (284.52 eV) is considered, the binding energy of the TiN 2p 3/2 peak is brought closer to 455.3 eV while the binding energies of other phases still fall within the possible ranges. The TiC, TiON, and TiO 2 2p 3/2 peaks are fitted to center around 455.1, , 457.2, ,, and 458.5 eV. …”
Section: Resultssupporting
confidence: 47%
“…Nevertheless, extensive effort was made in this study to meet the constraints on peak position, doublet separation and doublet area ratio simultaneously as much as possible. It should be noted that centering the TiN 2p 3/2 peak at around 455.85 eV, , near the upper limit of the possible range, produced the best fitting overall for our data, even though some studies have fitted the same peak to around 455.3 eV. , In addition, when the difference in the C–C binding energy between the values in this study (284.6–285.1 eV for samples produced at plasma powers at or above 75 W) and the value suggested in the detailed study on adventitious carbon contamination on TiN films (284.52 eV) is considered, the binding energy of the TiN 2p 3/2 peak is brought closer to 455.3 eV while the binding energies of other phases still fall within the possible ranges. The TiC, TiON, and TiO 2 2p 3/2 peaks are fitted to center around 455.1, , 457.2, ,, and 458.5 eV. …”
Section: Resultssupporting
confidence: 47%
“…Several authors have demonstrated with different techniques that the compound thin film which grows on the target has a thickness in the or-der of a few nanometer [15,16,[18][19][20]. The effective formation rate of the compound rate can be calculated based on the difference between the growth R ox and sputter rate R sp ,…”
Section: Calculationsmentioning
confidence: 99%
“…Monte Carlo simulations demonstrated that these ions are implanted in a layer of a few nanometer thick (see e.g. [13][14][15][16]).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain this effect such as an efficient cleaning of the target during the HiPIMS pulse [89], reduced target oxidation due to stronger gas rarefaction for discharge with high Ipk [90] and covering of the reacted areas in the target by the returning metal ions [91]. It has also been found that N atoms are embedded deeper into the Ti surface when using HiPIMS as compared to DCMS [92], which could decrease the deposition rate and alter the point at which the transition mode is observed as well as the hysteresis behavior. Common process parameters used for monitoring the reactive sputtering process are the deposition rate and the reactive gas partial pressure as shown in Fig.…”
Section: Ion Energy Distribution Function (Iedf)mentioning
confidence: 99%